The Indian in the cupboard - Banks, Lynne Reid, 1929- (New York : HarperTrophy, 2003)
A nine-year-old boy receives a plastic Indian, a cupboard, and a little key for his birthday and finds himself involved in adventure when the Indian comes to life in the cupboard and befriends him.
5.0
3-6
Keywords: Indians of North America -- Juvenile fiction; Magic -- Juvenile fiction; Toys -- Juvenile fiction; Indians of North America -- Fiction; Magic -- Fiction; Toys -- Fiction; Magic -- Fiction; Native Americans -- North America -- Fiction; Toys -- Fiction